2010
DOI: 10.36487/acg_rep/1063_13_belem
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent failure criterion for cemented paste backfills

Abstract: In this paper, a simple time-dependent failure criterion has been proposed for cemented paste backfills. In addition to curing time, it allows to take into account the binder content that will be responsible for the material strength development. The properties described by this time-dependent criterion are those undrained since the backfilled mine stopes have been categorised as undrained in long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Studies on Kidd tailings [33] and Williams tailings [35] found backpressures of at least 400 kPa were required for saturation. Therefore, tests by [36][37][38] at higher confining pressure levels would result in closer to saturated conditions. However, as shown in Figure 12, the mobilized shear resistance in undrained testing is not as high as in drained testing.…”
Section: Discussion: Application At Other Mine Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on Kidd tailings [33] and Williams tailings [35] found backpressures of at least 400 kPa were required for saturation. Therefore, tests by [36][37][38] at higher confining pressure levels would result in closer to saturated conditions. However, as shown in Figure 12, the mobilized shear resistance in undrained testing is not as high as in drained testing.…”
Section: Discussion: Application At Other Mine Sitesmentioning
confidence: 99%
“…This result is inconsistent with results of [33] which used backpressure saturation and pore water pressure measurements when testing the same Kidd CPB. The authors in [36] note that results from tests without backpressure saturation and pore water pressure measurements must be used carefully in design and could lead to overestimating backfill strength in some cases. Estimating plug strength requirements is such a case, where using c = 1 2 UCS would reduce the calculated strength (UCS) requirement by a factor of two.…”
Section: Discussion: Application At Other Mine Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…These eco-binders can contain treated biomass ashes, calcined clays, or any other industrial by-product that can be reused. For this purpose, the relative hydration index (Ha) was defined as follows (Belem & Sahi 2017;Sahi et al 2015, Belem et al 2010):…”
Section: Procedures For the Selection Of The Type Of Binding Agentmentioning
confidence: 99%
“…Cemented paste backfill (CPB) is an economic and environmental friendly technique applied in underground mining for supporting surrounding rock and replacing the pillar [1][2][3]. Over the years, the CPB technology has been widely adopted in the mining industry around the world [4][5][6]. CPB is usually composed of thickened or filtered tailings from concentrating mills, binding materials, and mixing water.…”
Section: Introductionmentioning
confidence: 99%